An investigation of the Sowetan "enough is enough-take back your dignity" campaign to challenge violence against women and children - Ndabezitha, Nomthandazo Sibusisiwe Mary-Angel (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2017)
This investigation of the Sowetan "Enough is Enough - take back your dignity" campaign to challenge sexual violence explores whether the South African daily newspaper's sustained anti-rape coverage challenges or reinforces the social order. It locates the Sowetan campaign's response within two troubling contradictions. First, while South Africa is a democracy with arguably the most liberally progressive constitution in the world, the epidemically high rape statistics indicate that South African women and children inhabit an environment in which they are effectively denied the same freedoms and rights as men. The Sowetan anti-rape campaign responds to this paradox. Second, heightened exposure and coverage in the news media of rape incidents do not seem to correlate directly with a decrease in incidents of sexual violence. My observation of these contradictions leads me to question whether the anti-rape campaign can be socially transformative. Informed by the Foucauldian insights that the meaning of things is not inherent but exists in discourse, which has the power to make itself true, this study investigates what discourses are articulated in the representation of masculinities and femininities. In this regard, my investigation is informed by cultural studies and gender studies theories. Recognising rape as an enactment of a particular type of masculinity makes it clear that rapists are not deviant monsters, but are men embodying a discourse of male sexual entitlement legitimated by the social order. As the campaign coverage largely represents rape in historically black locations such as townships and villages, I argue that rape is an enactment of a particular violent masculinity within a particular socio-economically marginalised postcolonial context. Hence I also use postcolonial studies and gender studies to inform my theory. This qualitative research takes the form of a case study which entails a critical discourse analysis of 19 texts purposively sampled in order to identify whether the campaign challenges or reinforces the social order. I argue that rehearsing the narratives of prevalent rape and horror at this epidemic without addressing the social order of gender inequality that enables rape is inadequate. The findings indicate that the campaign has limited socially transformative potential, as, while it sometimes challenges the discourse of female passivity, it does not go so far as to critically engage with masculinities and questioning how violent ones are produced in the social order.
Keywords: Uncatalogued